KEGANASAN DAN ISLAM: ANALISIS KONSEP JIHAD - Abd Majid, Mahmood Zuhdi (Jurnal Syariah, 2019)
This article is an analytical discussion on terrorisme according to the principles of Islamic jihad. The conclusion reached by the analysis was that even though principally the violence is contrary to the Islamic teaching but in certain conditions, such as defending rights violated by others, there will be some considerations.